Decisions Support System About The Granting Aid of Machinery Ketinting for The Fisher From Bajo Village Uses The Method Additive Ratio Assessment - Aswar; Anto; Hamria (Explorer, 2023)
Abstract− This study aims to design a decision support system for providing tinting machine assistance for fishing communities in Bajo village. As well as selecting the provision of getting machine assistance. The method used in this study is the additive ratio assessment (ARAS) method. The ARAS method is used in this study because it can rank by comparing one alternative with another to provide more precise and accurate results. The results obtained in this study are the results of determining the highest recipients of getting machine assistance obtained in the calculation of the ARAS method so that the value of the ranking can provide information about the beneficiaries of the tinting machine assistance.